2023
DOI: 10.1177/17589983231155270
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation following extra-articular proximal phalangeal fractures of the fingers in adults: a scoping review

Abstract: Introduction Proximal phalangeal fractures are common and can have a significant impact on hand function. Therefore, it is important to optimise post-operative rehabilitation. A scoping review was undertaken to map the existing evidence on rehabilitation of proximal phalangeal fractures of the fingers in adults. Methods A comprehensive search was conducted which included database searching, reference searching, hand searching of journals, and searching for grey literature. Eight articles were included after sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This is the first systematic review to the authors’ knowledge which provides a focused overview of conservatively managed extra-articular P1 fractures in adults, and supports previous studies in this domain. A recent scoping review by Vervloesem et al 22 in 2023 identified current methods of rehabilitation following conservative and surgical methods of management for extra-articular P1 fractures. It included 267 fractures from eight articles, five of which examined conservative interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first systematic review to the authors’ knowledge which provides a focused overview of conservatively managed extra-articular P1 fractures in adults, and supports previous studies in this domain. A recent scoping review by Vervloesem et al 22 in 2023 identified current methods of rehabilitation following conservative and surgical methods of management for extra-articular P1 fractures. It included 267 fractures from eight articles, five of which examined conservative interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study are similar to those identified in two previously published reviews. 21 , 22 The included articles had significant variability in study design and poor reporting quality. The orthotic design and duration of wear differed greatly between studies, often with little justification.…”
Section: Discussionmentioning
confidence: 99%